Exploring the Protective Value of Using Sexting for Condom Negotiation on Condom use Determinants and Practices Among Forcibly Displaced Adolescents in the Slums of Kampala, Uganda - Okumu, Moses; Logie, Carmen H.; Ansong, David; Mwima, Simon; Hakiza, Robert; Newman, Peter A. (AIDS and behavior, 2022)
Given the global growth of adolescent texting, we evaluate texting-based sexual communication as a potential site for interventions encouraging condom use cascades, particularly among displaced adolescents—a population with disproportionate levels of sexually transmitted infections, including HIV. With data from 242 forcibly displaced adolescents in the slums of Kampala, Uganda, we used path analysis to examine pathways from gender/dating relationship to condom determinant (knowledge of where to access condoms) and practices (access/use of condoms), through sexting-based condom negotiation, controlling for sexting practices. We found direct pathways from gender (boys vs. girls) and from dating relationship (dating vs. not) to condom determinant. Sexting-based condom negotiation partially mediated the pathway from gender/dating relationship to condom determinant, and fully mediated the pathways from gender/dating relationship to condom practices. Future digital sexual health interventions should consider the utility of texting-based applications in promoting knowledge and use of condoms among adolescents.